Pengaruh Market Value Added (MVA), Net Profit Margin (NPM) Dan Return On Equity (ROE) Terhadap Harga Saham Pada Perusahaan Telekomunikasi Yang Terdaftar Di BEI - Suhatina, Suhatina; Amani, Tatik; Priantono, Seger (Ecobuss, 2025)
This research aims to examine the influence of Market Value Added (MVA), Net Profit Margin (NPM) and Return On Equity (ROE) on share price in Telecommunications companies listed on the IDX. The type of research used is quantitative. The population of this research is the Telecommunications companies listed on the IDX. Sample selection was carried out using purposive sampling technique. The selected sample was 10 companies. The analytical method used include the classical assumption test, multiple linear regression analysis test, coefficient of determination, t- test, F-test and dominant test. The research results show that partially Market Value Added (MVA), and Return On Equity (ROE) have a significant effect on share price, while the Net Profit Margin (NPM) have a insignificant effect on share price. Simultaneously Market Value Added (MVA), Net Profit Margin (NPM) dan Return On Equity (ROE) have a simultaneously effect on share price. Market Value Added (MVA) have a dominant influence on share price.